Islam Nusantara and Religious Peacemaking: Nahdlatul Ulama’s Ideas in Creating Peace in Afghanistan - Mu'min Mu'min; Dina Yulianti; Otong Sulaeman (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2021)
The socio-political crisis in Afghanistan shows a surprising consequence, especially after the return of the Taliban in seizing the country after being overthrown by the United States (US) in 2001. The international community has pursued peace negotiations for the last ten years. Indonesia, however, has played a significant role in reconciling the factions in Afghanistan by involving religious organizations, in this case, Nahdlatul Ulama (NU). Religious narratives cannot be excluded in conflict resolution because the Taliban use religious justification in their actions. This study aims to uncover the religious narratives used by NU to calm down the opposing factions, including the Taliban. The qualitative research method used is interviews with the key informants and supported by various sources. This study finds that Nahdlatul Ulama has contributed to peace with a religious approach, namely peace hermeneutics and empathy detachment. In its implementation, NU uses religious narratives of Islam Nusantara. In addition, NU has also succeeded in creating capacity, institution building, and agreement among the conflicting factions.